Managing the Future Imaginary: Does ‘Post-Normal’ Science need Public Relations? (RT. A Journal on Research Policy and Evaluation, 2018)
Contemporary conditions of so-called ‘post-normal’ science characterised by fundamental uncertainty and high decision stakes have been met by the call for an ‘extended peer community’ to include a full range potential stakeholders in the assessment and evaluation of future research policy (Functowicz and Ravetz, 1993; 1994). Correspondingly, the term ‘Anticipatory Governance’ (AG) has entered currency within Science and Technology Studies (STS) circles, where the phrase refers sympathetically to the fields involvement with an array of novel practices routinely carried-out in the name of increasingly public-focused, conscientious management of emerging science and technology. Existing literature in this area has typically focused on perceived benefits of social-scientist driven AG as ‘Real Time Technology Assessment’ (RTTA), rather than address how such participation — in line with STS’s contemporary post-social, object-centred, anti-normative research character — relates to a lack of institutional protection for most STS practitioners today. I argue the activities of social science researchers enrolled in AG-styled programmes appears to closely resemble those of PR professionals, and as such, in today’s knowledge economy the field could have much to gain by turning to clarify and formalise the unique cognitive-base and normative horizons befitting of a closed occupational group. I suggest an occupational restructuring in line with the ‘professional project’ (Macdonald, 1995) could bring about increased autonomy for STS practitioners, as well as purposeful direction for future research.
Keywords: post-normal science; anticipatory governance; science and technology studies; public engagement; technology assessment